Implementasi nilai toleransi tingkat elementary school di jungle school kota salatiga - Mega Herawati; Hasan Mahfud; Roy Ardiansyah (Universitas Sebelas Maret, 2022)
Tolerance is a way of thinking that can be translated into an act of mutual openness, mutual respect, character or attitude of respect for different positions and / or contrary to their position as a necessity for a pluralistic nation. The implementation of theTolerance Value Elementary Level in the Jungle School of Salatiga City can be seen when the learning is carried out. Teaching and learning activities are carried out as a form of habituation to create the implementation of the value of tolerance, so that the Jungle School creates a peaceful and tolerant atmosphere. This research is a qualitative research with a case study method. Jungle School was chosen as the subject in this study. Data analysis in the study used an interactive model analysis technique by Miles and Huberman. The results of this study indicate that the implementation of the value of tolerance has been carried out well in the Jungle School with an indication that all aspects of tolerance have been carried out.